1990
DOI: 10.1111/j.1472-765x.1990.tb01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to a lysine medium for detection of salmonellas by elctrical conductance

Abstract: Improvements in performance of a lysine conductance medium for the detection of salmonellas were achieved from a study of the effects of its various components. When sodium biselenite was included as an inhibitor for non‐salmonella organisms conductance signals were depressed. The inclusion of sodium chloride reduced this toxicity and improved conductance responses. Increasing the pH to pH 7.0 prevented the medium becoming too acidic and inhibitory to salmonellas. The new medium detected 70‐0% of salmonella‐po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Impedance microbiology measures the variations in electrical impedance of a culture medium or a reactive solution that results from the bacterial growth [ 55 , 88 ]. Previous studies have reported the use of this technique to detect and quantify different species of bacteria [ 14 , 89 , 90 ] such as Salmonella [ 91 , 92 , 93 ], E. coli [ 94 , 95 ], Listeria innocua and Listeria monocytogenes [ 96 ], Staphylococcus aureus [ 97 ], Enterococcus faeccalis [ 98 ], coliforms, Listeria spp., and L. monocytogenes [ 55 ]. Detection times ranging from 24 hours [ 99 ] to seconds [ 100 ] have been reported.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Impedance microbiology measures the variations in electrical impedance of a culture medium or a reactive solution that results from the bacterial growth [ 55 , 88 ]. Previous studies have reported the use of this technique to detect and quantify different species of bacteria [ 14 , 89 , 90 ] such as Salmonella [ 91 , 92 , 93 ], E. coli [ 94 , 95 ], Listeria innocua and Listeria monocytogenes [ 96 ], Staphylococcus aureus [ 97 ], Enterococcus faeccalis [ 98 ], coliforms, Listeria spp., and L. monocytogenes [ 55 ]. Detection times ranging from 24 hours [ 99 ] to seconds [ 100 ] have been reported.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The work of Bolton (1990) has already shown the indirect technique to be a powerful tool for working with strains of Staph. aureus, Listeria monocytogenes, Enterococcus faecalis, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Aeromonas hydrophila and Salmonella spp.…”
Section: Indirect Impedancementioning
confidence: 99%
“…The modified lysine medium was not as sensitive as S C / T / D for the detection of salmonella from animal feeds (70% of impedance positive samples). However, it was proposed that both S C / T / D and lysine media should be used in impedance procedures (Smith et al 1990). Davda and Pugh (1991) developed a modified ornithine decarboxylase broth and a selenite cystine trimethylamine oxide deoxyribose medium to improve selection and detection of salmonellae.…”
Section: Salmonella Detectionmentioning
confidence: 99%
“…Greater impedance changes were obtained with mannitol or deoxyribose in place of dulcitol (Pettipher and Watts, 1989a). Other Salmonella impedance medium for selective growth between genus, species, and strain were developed by several research groups (Ogden, 1988;Bullock and Fordsham, 1989;Pettipher and Watts, 1989b;Simth et al, 1990;Davda and Pugh, 1991). Blivet et al (1998) developed a new impedance medium that supported the growth of Salmonella serotypes and inhibited non-Salmonella strains in pure culture.…”
Section: Classic Impedance Microbiologymentioning
confidence: 99%